Case study: Menara Kementerian Belia dan Sukan Putrajaya / Muhammad Haziq Pauzi ...[et al.] - Pauzi, Muhammad Haziq; Ismail, Mohd Izzat Fahmi; Zamhuri, Mohamad Zaidi; Mohd Razali, Nursaara; Ahmad Zamzamir, Noor Syazwanis (2015)
Ministry of Youth and Sport Tower, Putrajaya is classified as a government office building that located at a strategic place among others government development area. This chapter describes about building detail, building view, location plan, building owner, company logo interpretation, surrounding area, adjacent building, building accommodation, the purpose of the building, and facilities provided in the building. KBS building is classified as a high-rise building with two basements. This building is constructed in the midpoint of the Putrajaya government development area. Furthermore, this chapter also explained on the space functional and gross floor area in each floor in KBS building.